2021
DOI: 10.1590/2177-6709.26.6.e212069.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress relaxation in beta-titanium cantilevers used in orthodontic mechanics

Abstract: Objective: This study evaluated the force decay and design shape changes caused by stress relaxation in two different orthodontic cantilever configurations. Methods: Eighty cantilevers made of 0.017 x 0.025-in beta-titanium wires were standardized in a passive position, using real scale templates, and randomly divided into two groups (n = 40): Type 1 and Type 2. Each group received a different design (Type 1 with three bends, and Type 2 with two bends), and both were divided in four subgroups (n = 10) accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…They concluded that the design of the cantilever and proximity of the bends influenced the force decay pattern over time. Cantilevers activated at the distal part—similar to our study—presented a more stable design in the first weeks compared to the activation located at the bend located inferiorly at the utility shape [ 27 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…They concluded that the design of the cantilever and proximity of the bends influenced the force decay pattern over time. Cantilevers activated at the distal part—similar to our study—presented a more stable design in the first weeks compared to the activation located at the bend located inferiorly at the utility shape [ 27 ].…”
Section: Discussionmentioning
confidence: 77%
“…Bilinska and Dalstra (2022) evaluated in vitro the resultant horizontal and vertical forces, delivered with asymmetric and symmetric loading of the frontal segment with regard to possible use for midline correction [26]. A study by Jacob et al appraised the force decay and design shape changes caused by stress relaxation in two different orthodontic cantilever configurations [27]. Specific cantilever shapes and forms influence the delivered force system.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a curved cantilever provides combined retraction and intrusion, while utility-shaped produces protrusive and intrusive forces [ 6 , 7 ] ( Figure 1 ). In addition, the point of activation influences the force decay pattern over time [ 8 ].…”
Section: Introductionmentioning
confidence: 99%